Left-to-right rotated single lung transplant. (27th July 2022) - Chida, Masayuki; Inoue, Takashi; Araki, Osamu; Maeda, Sumiko
Abstract: We successfully performed left-to-right rotated single lung transplants in 2 patients. For this procedure, the left pulmonary artery of the donor undergoes a U-shaped turn with A3 at the bottom to anastomose with the recipient's right pulmonary artery in front of the bronchus. It is extremely important to avoid kinking the pulmonary artery at the site of the U-shaped turn. Abstract : A single lung transplant remains the procedure of choice for certain patients because of the critical donor shortage.